Pengaruh Pengendalian Internal dan Kompensasi Terhadap Kinerja Pengrajin Dengan Motivasi Sebagai Variabel Intervening (Survei pada Pengrajin Batik di Kota Jambi) - Netty Herawaty; Rizky Yulisari (Universitas Batanghari, 2019)
The purpose of this study was to determine and analyze whether there is an influence of internal control and compensation for the performance of craftsmen, to find out and analyze whether there is an influence of internal control and compensation for motivation, to know and analyze whether there is a motivational influence on the performance of craftsmen and to know and analyze whether there is an influence of internal control and compensation for the motivation and performance of craftsmen. This study uses a multiple regression analysis tool. This study uses primary data. Respondents in this study were batik craftsmen. The results of this study indicate that internal control, compensation and motivation simultaneously show a significant influence on the performance of craftsmen. The influence of internal control and compensation is directly greater than the indirect effect on performance through work motivation, so it can be concluded that work motivation does not become a variable mediating between internal control and compensation for the performance of batik craftsmen.